Implementation of the Istishna Contract in Mrs. Zami's Sewing Business - Zami Salsabela; Muhammad Syarofi (Al-Abqori: Journal of Islamic Thought Studies, 2025)
The istishna' contract is a form of sale and purchase contract in which someone orders the manufacture of certain goods with specifications and conditions that have been agreed upon between the orderer and the seller. The aim of this research is the application of the Istishna contract in the sewing business to create transactions that are fair, transparent and in accordance with sharia provisions, while ensuring that accounting records are carried out in accordance with the standards regulated in PSAK 104. This research method aims to use a descriptive qualitative approach with a study method case, which focuses on Mrs. Zami applies the Istishna agreement in their transactions. The research results explain that Mrs. Zami has implemented the mudharabah contract in providing satisfactory service and results to customers, from implementing the ishtisna contract in his sewing business. Zami is a place that provides a wide choice of concepts and models, ranging from formal to non-formal. Mrs. Zami has implemented the ishtishna contract as a growth financing solution with the balance sheet financial report obtaining total assets of 2,925,000 and total liabilities of 2,925,000. Meanwhile, for the financial report, the change in capital which previously amounted to 1,450,000 in November became 2,925,000, with a total net profit obtained of 1,475,000. Novelty of the results of this research found that the application of the ishtishna contract as a financing solution for Mrs. Zami.